MEMPOSISIKAN MASYARAKAT SEBAGAI GARDA DEPAN PELESTARI SUMBER DAYA ARKEOLOGI - nfn Wasita (Balai Arkeologi Kalimantan Selatan, 2007)
Indonesian archaeologists are challenged by the huge number of cultural heritage that to be conserved. Concerning with this, the involvement of people surrounding the heritageÂ places, as one of instrument of conservation, is very important. However, innovation in method and strategy to increase the people awareness in any conservation activities are still to be done.